2011
DOI: 10.1097/aog.0b013e31821aa720
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Fetal Tricuspid Regurgitation in First-Trimester Screening for Major Cardiac Defects

Abstract: Assessment of flow across the tricuspid valve improves the performance of screening for major cardiac defects by fetal nuchal translucency and ductus venosus flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
1
12

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(123 citation statements)
references
References 31 publications
2
108
1
12
Order By: Relevance
“…1,4,13,14 To our knowledge, this article is the first practical description of a straightforward and direct screening method for congenital heart defects in the first trimester. In this study we found that our simple firsttrimester cardiac protocol was an effective screening method for congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,4,13,14 To our knowledge, this article is the first practical description of a straightforward and direct screening method for congenital heart defects in the first trimester. In this study we found that our simple firsttrimester cardiac protocol was an effective screening method for congenital heart defects.…”
Section: Discussionmentioning
confidence: 99%
“…They were based on markers of aneuploidy, including nuchal translucency, triuspid regurgitation, and ductus venosus velocimetric parameters. [1][2][3][4] However, the detection rates for congenital heart defects do not exceed 40% for nuchal translucency above the 95th percentile alone and 58% for nuchal translucency above the same limit combined with a reversed or absent a-wave in the ductus venosus flow profile. 1 Objectives-The first goal of this study was to analyze the diagnostic performance of the 4-chamber view, 3-vessel and trachea view, and their combination in color mapping during early cardiac evaluations for selecting cases suspicious of congenital heart defects.…”
mentioning
confidence: 98%
“…For example, cardiac function assessment has proven utility in the differential diagnosis of cardiomyopathies 60 or prediction of perinatal mortality in congenital heart disease 61 . Similarly, first‐trimester DV and tricuspid regurgitation assessment has an additional predictive value for Down syndrome and congenital heart disease 62 . In addition, some cardiac parameters with high sensitivity such as MPI or annular peak velocities have shown promising results in monitoring and predicting outcome in intrauterine growth restriction 9 , 58 or congenital diaphragmatic hernia 5 .…”
Section: Discussionmentioning
confidence: 99%
“…In view of the low detection rates for certain abnormalities -particularly for cardiac defectsin the 2nd trimester, the use of surrogate markers for abnormalities detectable in the 1st trimester should not become less important [15]. A study which included approximately 40 000 normal pregnancies and 85 foetuses with serious cardiac defects showed that combining the assessment of nuchal translucency with that of blood flow in the ductus venosus and through the tricuspid valve in the 12+ week of gestation resulted in the detection of around 60 % of all cardiac defects [16]. It has also been shown that the risk for numerous pregnancy complications can be assessed around 12+ weeks of gestation.…”
Section: Studymentioning
confidence: 99%